2022
DOI: 10.1101/2022.05.18.492405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mating disrupts morning anticipation inDrosophila melanogasterfemales

Abstract: After mating, the physiology of Drosophila females undergoes several important changes, some of which are reflected in their rest-activity cycles. To explore the hypothesis that mating modifies the temporal organization of locomotor activity patterns, we recorded the fly activity by a video tracking method. Monitoring rest-activity patterns under light/dark (LD) cycles indicated that mated females lose their ability to anticipate the night-day transition, in stark contrast to males and virgins; this postmating… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…So far our analysis identified networks that respond to SP, but it did not give information about how SP coordinates changes across networks. Because a non-SP aspect of mating (in the first 4 h postmating) and SP (after 4 h) up-regulated the expression of Clk, and because SP influences behaviors that are under circadian control ( 16 , 17 ), we investigated whether additional features with circadian rhythms were differentially expressed after mating. We found that of the 1,305 differentially expressed features from the network analysis, 18% (232 features) follow a circadian rhythm in V females ( q-value <0.3, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far our analysis identified networks that respond to SP, but it did not give information about how SP coordinates changes across networks. Because a non-SP aspect of mating (in the first 4 h postmating) and SP (after 4 h) up-regulated the expression of Clk, and because SP influences behaviors that are under circadian control ( 16 , 17 ), we investigated whether additional features with circadian rhythms were differentially expressed after mating. We found that of the 1,305 differentially expressed features from the network analysis, 18% (232 features) follow a circadian rhythm in V females ( q-value <0.3, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since synaptic connections exist between pC1 neurons and clock neurons, there is a possibility for SP to directly modulate the female’s clock, thereby allowing SP to control many different postmating responses at once. Through ppk+ neurons that express SPR, SP alters neurotransmitter release from central clock ventral lateral (LNv) neurons, leading to loss of predawn elevated activity in mated females ( 17 ). LNv are called “morning neurons”, and LNd (for which we found a direct connection with pC1) are called “evening neurons” ( 106 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation